Damage detection in a free-free beam structure using reconstructed mode shape data: Experimental approach - Fawazi, Noor; Man, M. H.C.; Parnon, Mohamad Afiq Amiruddin (2023)
Experimental modal testing was used to discover a crack in a beam structure in this study. Minor changes in beam geometry can theoretically alter vibration response. In fact, comprehensive information about the presence of small cracks is unlikely to be detected only from the experimental vibration response. As a result, looking at the vibration mode shape data alone isn't enough to identify the crack. The mode shape data, which contains information on the crack effects present in the beam structure, was collected through experimental modal testing. The difference between two sets of detail coefficients computed from the reconstructed mode shape data using the Stationary Wavelet Transform then reveals the position of the cracked beam (SWT). The reconstructed mode shape data is first interpolated with spline interpolation to capture the existence of the crack position with better resolution. The difference between two sets of detail coefficients from the SWT is visualised using splined interpolation, which can be particularly useful in overcoming the issue of a limited number of measuring points during actual modal testing.